Benefit with methylprednisolone in continuous pulsetherapy in progressive primary form of multiple sclerosis: study of 11 cases in 11 years Benefício do uso de pulsoterapia contínua com metilprednisolona na forma primária progressiva da esclerose múltipla: estudo de 11 casos em 11 anos - Edmar A.S. de Araújo; Marcos R. Gomes de Freitas (Arquivos de Neuro-Psiquiatria)
Primary progressive multiple sclerosis (PPMS) is defined clinically with a progressive course from onset. There is no approved treatment for the PPMS. Methylprednisolone IV (MP) hastens the recovery from MS relapses. We studied 11 patients that met the MacDonald's diagnostic criteria for PPMS. The dose of MP was 30 mg/kg in 250 mL of glucose solution in three consecutive days during the first week, two doses during the second and one dose in the third week. One weekly session for eight consecutive weeks was given. After, a once-a week/eight-week interval was maintained. The medium EDSS before treatment was 6.2, and after 11.2 years of treatment, the EDSS was 4.9. Although we studied a small sample of PPMS we may conclude that therapy with IVMP prevents clinical worsening of MS in the majority of patients with improvement in EDSS scores. A forma progressiva da esclerose múltipla (FPEM) é definida como progressiva desde o início. Não há tratamento eficaz para esta forma. A metilprednisolona por via endovenosa (MPEV) é usada para os surtos de exacerbação da EM. Estudamos 11 pacientes que preenchiam os critérios de MacDonald para FPMS. A dose inicial de MPEV foi de 30 mg/kg em 250 mL de soro glicosado por três dias consecutivos na primeira semana, duas doses na segunda e uma dose na terceira semana. Seguiu-se uma sessão semanal por oito semanas. Após manteve-se uma dose semanal a cada oito semanas. A média do EDDS foi 9,6 antes e 4,9 após 11,2 anos de tratamento. Embora tenhamos estudado número reduzido de casos, podemos dizer que o uso de MPEV impede a progressão da FPEM na maioria dos pacientes estudados com melhora do EDDS.